Could METS-VF provide a clue as to the formation of kidney stones? - Guo, Zhenyu; Li, Guoxiang; Chen, Yan; Fan, Shuai; Sun, Shuai; Hao, Yunwu; Wang, Wei (Frontiers in Endocrinology, 2023)
Objective: The lifetime occurrence rate of kidney stones is 14%, making it one of the most prevalent urological conditions. Other contributing elements, such as obesity, diabetes, diet, and heredity, are also taken into account. Our research sought to explore the potential link between high visceral fat scores (METS-VF) and the occurrence of kidney stones, as a means of understanding how to prevent them.